1999
DOI: 10.1159/000023461
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Supplementation Increases the Level of Serum Insulin-Like Growth Factor-I but Does Not Promote Growth in Infants with Nonorganic Failure to Thrive

Abstract: We investigated in a randomized double-blind placebo-controlled study the effects of zinc supplementation (2 mg/kg/day) for 12 weeks on growth, serum insulin-like growth factor-I (IGF-I) and insulin-like factor binding protein-3 (IGFBP-3) on 3- to 9-month-old infants with nonorganic failure to thrive (NOFTT). 25 infants completed the study, 14 received zinc supplementation (group A), and 11 received placebo (group B). The control group for baseline measurements was composed of 10 age-matched normal growing inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 28 publications
0
11
1
Order By: Relevance
“…Our findings were supported by other studies [3-5,17,18] who reported that Zn supplementation was effective for inducing growth in short children with Zn deficiency in a rate similar to that in healthy children. However, in some studies, this effect was not observed [6,7]. Ninh et al [19] showed that Zn supplementation increased both weight and height after five months compared with placebo treatment but this was not the case in our study concerning the weight.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Our findings were supported by other studies [3-5,17,18] who reported that Zn supplementation was effective for inducing growth in short children with Zn deficiency in a rate similar to that in healthy children. However, in some studies, this effect was not observed [6,7]. Ninh et al [19] showed that Zn supplementation increased both weight and height after five months compared with placebo treatment but this was not the case in our study concerning the weight.…”
Section: Discussioncontrasting
confidence: 84%
“…Some studies have reported positive effects of Zn supplementation on growth in various groups of Zn-deficient children [3-5]. However, in some studies, this effect was not observed [6,7]. …”
Section: Introductionmentioning
confidence: 99%
“…It is now known that in mossy fiber terminals, as well as in other brain regions, vesicular zinc colocalizes in neurons using glutamate as a neurotransmitter (Beaulieu et al, 1992;Frederickson, 1989). The concentration of zinc within these vesicles has been estimated to be as high as millimolar levels (Assaf and Chung, 1984;Frederickson et al, 2000;Howell et al, 1984;Qian and Noebles, (Mackenzie and Oteiza, 2007;Telford and Fraker, 1995;Truong-Tran et al, 2000) Audition (Frederickson et al, 1988;Rubio and Juiz, 1998) Free radical management (Bray and Bettger, 1990;Powell, 2000;Prasad et al, 2004;Zago and Oteiza, 2001) Hormone activity (Hershkovitz et al, 1999;MacDonald, 2000;McNall et al, 1995) Immune efficiency (Fraker et al, 2000;Prasad, 1995Prasad, , 2008Rink and Kirchner, 2000;Ibs and Rink, 2003) Intracellular signaling (Cousins, 1998;Frederickson et al, 2005a,b;Prasad, 1995;Vallee and Auld, 1993) Learning and memory (long-term potentiation) Kodirov et al, 2006;Lu et al, 2000;Saito et al, 2000;Takeda et al, 2009) Motor coordination (Jo et al, 2000b;Vincent and Semba, 1989) Neurogenesis (Dvergsten, 1984a;Frederickson et al, 2000) Neuromodulation (Colvin et al, 2003(Colvin et al, , 2008Kay and Toth, 2008;…”
Section: Discovery Of Gluzinergic Neuronsmentioning
confidence: 99%
“…The requirement for zinc is most intimately linked to its vital role in regulating numerous aspects of cellular metabolism, including immune (Fraker et al, 2000;Prasad, 1995Prasad, , 2008Rink and Kirchner, 2000), protein (Vallee and Falchuk, 1993), hormone (Hershkovitz et al, 1999;MacDonald, 2000;McNall et al, 1995), antioxidant (Bray and Bettger, 1990;Powell, 2000;Prasad et al, 2004;Zago and Oteiza, 2001), transcription, and replication functions (Cousins, 1998;Vallee and Falchuk, 1993). On the other hand, overabundant levels of zinc can be cytotoxic, inducing apoptosis (Ibs and Rink, 2003;Mackenzie and Oteiza, 2007;Telford and Fraker, 1995) and neuronal death (Koh et al, 1996;Sensi and Jeng, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported positive effects of Zn supplementation on growth in various groups of Zn-deficient children [33][34]. However, in some studies, this effect was not observed [35][36]. We aimed to assess GH-IGF-Zn axis in short children.…”
Section: Discussionmentioning
confidence: 99%